Effect of bromelain treatment on some chemical and microbiological properties of pastrami during storage period - Ümit Gürbüz; Yusuf Doğruer; Mustafa Nizamlıoğlu; Mustafa Atasever; Semra Kayaardı (Eurasian Journal of Veterinary Sciences)
This study was done to determine the effect storage period on chemical and microbiological properties of pastrami samples which prepared the meal samples applied various bromelain solutions (0.25, 0.50 and 1,0 %). Significant differences among the pastrami samples on the humidity. TBA and aw values were determined on the 1st. 30th and 60th days of experiment respectively. Microbiologically, the number of general, Staphylococcus-Micrococcus and Lactobacillus microorganisms of pastrami samples did not change significantly during the storage period. In conclution, it was determined that bromelain treatment did not effect on chemical and microbiological properties of pastrami samples during the storage period.